Changes in Glaciers and Glacial Lakes and the Identification of Dangerous Glacial Lakes in the Pumqu River Basin, Xizang (Tibet). (20th January 2014) - Che, Tao; Xiao, Lin; Liou, Yuei-An
Abstract : Latest satellite images have been utilized to update the inventories of glaciers and glacial lakes in the Pumqu river basin, Xizang (Tibet), in the study. Compared to the inventories in 1970s, the areas of glaciers are reduced by 19.05% while the areas of glacial lakes are increased by 26.76%. The magnitudes of glacier retreat rate and glacial lake increase rate during the period of 2001–2013 are more significant than those for the period of the 1970s–2001. The accelerated changes in areas of the glaciers and glacial lakes, as well as the increasing temperature and rising variability of precipitation, have resulted in an increased risk of glacial lake outburst floods (GLOFs) in the Pumqu river basin. Integrated criteria were established to identify potentially dangerous glacial lakes based on a bibliometric analysis method. It is found, in total, 19 glacial lakes were identified as dangerous. Such finding suggests that there is an immediate need to conduct field surveys not only to validate the findings, but also to acquire information for further use in order to assure the welfare of the humans.